Short-term response to light after the polar night in the Arctic kelps Alaria esculenta and Saccharina latissima - Cobos-Mateo, Pablo; López-Gordillo, Francisco Javier; Roza, Patricia; Wulff, Angela; Smerdou, Carlos (Elsevier, 2025)
The current absence of ice in early spring in a number of Arctic fjords allows sunlight to penetrate the water column about two months earlier than it used to be when a thick ice cover was present. This can potentially change the growth dynamics of permanent seaweed forests. To elucidate the ability of seaweeds to take advantage of this early available light, growth, photosynthetic performance, and biochemical composition has been analyzed in two major forest-forming algal species, Alaria esculenta and Saccharina latissima, from Kongsfjorden (Svalbard) collected in early February, and incubated in dim light and dark conditions. For A. esculenta, new tissue appeared during the last weeks of the polar night, so that the new and old tissues coexisted in the same individuals and were compared. Dim light triggered positive growth rates. The onset of light led to rapid (1 h) increase in the optimum quantum yield (Fv/Fm) in the new tissue of A. esculenta, while the old tissue and S. latissima increased their maximum photosynthetic electron transport rate (ETRm). The new tissue accumulated 3 to 5 times more internal nitrate than the old tissue, but it showed lower content of photosynthetic pigments. Dim light promoted changes in stored carbohydrates in A. esculenta while the total C:N:P ratios remained stable in both species. Furthermore, S. latissima responded to light by decreasing its ∂13C values, indicating some activation of its carbon concentrating mechanism. Overall, dim light showed the potential to trigger photosynthetic metabolism and growth as early as February.
Keywords: Biología marina; Cambios climáticos; Ártico; Algas marinas-Fisiología; Algas marinas-Composición; Fotobiología; Biochemical composition; Global warming; Ice-free; Kongsfjord; PAM fluorescence; Seaweeds; Svalbard